Insights into IGH clonal evolution in BCP-ALL: frequency, mechanisms, associations, and diagnostic implications - Darzentas, Franziska; Szczepanowski, Monika; Kotrová, Michaela; Hartmann, Alina; Beder, Thomas; Gökbuget, Nicola; Schwartz, Stefan; Bastian, Lorenz; Baldus, Claudia Dorothea; Pál, Karol; Darzentas, Nikos; Brüggemann, Monika (Frontiers in Immunology, 2023)
The malignant transformation leading to a maturation arrest in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) occurs early in B-cell development, in a pro-B or pre-B cell, when somatic recombination of variable (V), diversity (D), and joining (J) segment immunoglobulin (IG) genes and the B-cell rescue mechanism of VH replacement might be ongoing or fully active, driving clonal evolution. In this study of newly diagnosed BCP-ALL, we sought to understand the mechanistic details of oligoclonal composition of the leukemia at diagnosis, clonal evolution during follow-up, and clonal distribution in different hematopoietic compartments. Utilizing high-throughput sequencing assays and bespoke bioinformatics we identified BCP-ALL-derived clonally-related IGH sequences by their shared ‘DNJ-stem’. We introduce the concept of ‘marker DNJ-stem’ to cover the entirety of, even lowly abundant, clonally-related family members. In a cohort of 280 adult patients with BCP-ALL, IGH clonal evolution at diagnosis was identified in one-third of patients. The phenomenon was linked to contemporaneous recombinant and editing activity driven by aberrant ongoing DH/VH-DJH recombination and VH replacement, and we share insights and examples for both. Furthermore, in a subset of 167 patients with molecular subtype allocation, high prevalence and high degree of clonal evolution driven by ongoing DH/VH-DJH recombination was associated with the presence of KMT2A gene rearrangements, while VH replacements occurred more frequently in Ph-like and DUX4 BCP-ALL. Analysis of 46 matched diagnostic bone marrow and peripheral blood samples showed a comparable clonal and clonotypic distribution in both hematopoietic compartments, but the clonotypic composition markedly changed in longitudinal follow-up analysis in select cases. Thus, finally, we present cases where the specific dynamics of clonal evolution have implications for both the initial marker identification and the MRD monitoring in follow-up samples. Consequently, we suggest to follow the marker DNJ-stem (capturing all family members) rather than specific clonotypes as the MRD target, as well as to follow both VDJH and DJH family members since their respective kinetics are not always parallel. Our study further highlights the intricacy, importance and present and future challenges of IGH clonal evolution in BCP-ALL.